A fundamental equation - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2017)
Very important and instructive trigonometric equation is considered. The solutions from different manuals and reference books are examined, mistakes of these solutions are discovered. It is shown how to make the solution of the equation shorter, how to present the answer more visually.